Decision-Making for the Supply Chain Management in Conditions of Economic Turbulence - Elena A. Lavrinenko; Vladimir A. Kalugin; Elena A. Stryabkova; Yana Yu. Bondareva; Julia V. Lyshchikova (International Journal of Supply Chain Management, 2020)
Abstract— The decision-making process for supply chain management is complex and involves multiple people across multiple teams. This article deals with the problem of choosing an optimal management solution in a turbulent economy. We systematise new management risks in the context of a pandemic are systematized. A method for constructing an integral risk assessment function for managerial decision-making is proposed. We identify aneed for an expert community to make more informed decisions has been identified. The research propose a simulation of new management risks in the context of a pandemic is proposed. Specific supply chains are faced with the situation where they have to accept uncertainty but need to develop a strategy that enables them still to match supply and demand. Hence, this research works in this direction and identifies various supply chain strategies to match demand and supply efficiently and effectively.